Managing in the new normal: Positive management practices elicit higher goal attainment, goal commitment, and perceived task efficacy than traditional management practices in remote work settings. An experimental study - Monzani, Lucas; Mateu, Guillermo; Ripoll, Pilar; Lira, Eva; Peiro, José María (Frontiers in Psychology, 2022)
The COVID-19 global pandemic will likely change how organizations conduct business. For example, a white paper from McKinsey claims that flexible and remote work arrangements (e.g., "working-from-home") will become increasingly frequent in the "new normal" that will follow the COVID-19 pandemic. Our work is motivated by the premise that in a post-pandemic workplace, traditional management practices like unilaterally assigning goals and displaying contingent rewarding behaviors will likely be replaced by positive management practices. In this context, positive management practices include allowing employees to self-set their goals and displaying authentic leadership behaviors while managing them. However, whether these positive management practices are more efficient in sustaining performance is unknown. Our study benchmarked positive management practices against traditional management practices in a remote work environment, using three individual performance metrics: goal attainment, goal commitment, and perceived task efficacy. In a panel laboratory experiment consisting of a baseline measurement and two work sessions, we randomly assigned participants to an authentic vs. transactional leadership condition (amateur actor recording) and one of three possible goal-setting types (assigned, self-set, “do-your-best”). Our results show that participants in the authentic leadership x self-set goals condition outperformed all other experimental conditions. Further, a post-hoc analysis revealed a serial mediation effect of (a) goal attainment and (b) goal commitment at time 1 on perceived task efficacy reports at time 2.